Xinnaokang improves cecal microbiota and lipid metabolism to target atherosclerosis. (1st December 2021) - Yang, R.; Yin, D.; Yang, D.; Liu, X.; Zhou, Q.; Pan, Y.; Li, J.; Li, S.
Abstract: This study aims to explore the potential mechanisms of Xinnaokang in atherosclerosis treatment. Firstly, the active components of Xinnaokang were analysed by HPLC, which contains ginsenoside Rg1, puerarin, tanshinone, notoginsenoside R1, ammonium glycyrrhizate and glycyrrhizin. Network pharmacology analysis showed there were 145 common targets of Xinnaokang, including the chemical stress, lipid metabolite, lipopolysaccharide, molecules of bacterial origin, nuclear receptor and fluid shear stress pathways. Then, the animal experiment showed that Xinnaokang reduced the body weight and blood lipid levels of atherosclerotic mice. Vascular plaque formation was increased in atherosclerotic mice, which was markedly reversed by Xinnaokang. In addition, Xinnaokang reduced CAV‐1 expression and increased ABCA1, SREBP‐1 and LXR expressions in the vasculature. Xinnaokang promoted SREBP‐2 and LDLR expressions in the liver but decreased IDOL and PCSK9 expressions, indicating that Xinnaokang regulated lipid transport‐related protein expression. Cecal microbiota diversity was reduced in atherosclerotic mice but increased after Xinnaokang treatment. Xinnaokang treatment also improved gut microbiota communities by enriching Actinobacteria, Bifidobacteriales and Bifidobacteriaceae abundances. Metabolic profile showed that Xinnaokang significantly reduced homogentisate, phenylacetylglycine, alanine and methionine expressions in the liver of atherosclerotic mice. Xinnaokang effectively alleviated atherosclerosis, and this effect might be linked with the altered features of the liver metabolite profiles and cecal microbiota.